Pengaruh Arsitektur Hindu pada Masjid Menara Kudus - Ahnaf Aan; Velma Nindita (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
AbstractThe design of the Menara Kudus Mosque showcases a strong influence of Hindu architecture, making it an iconic example of cultural acculturation in Indonesia. This paper explores how Hindu elements shaped the mosque's design, using a descriptive method and a case study approach. The findings reveal that the minaret, the mosque's ornaments resembling Hindu temples, and its entrance gate similar to a candi bentar demonstrate a harmonious blend of Hindu and Islamic architecture. Sunan Kudus utilized cultural acculturation as an effective strategy to facilitate the local community's acceptance of Islam. This mosque serves not only as a religious center but also as a symbol of the integration of Hindu and Islamic values. This research contributes to the preservation of cultural heritage and promotes religious tolerance through architectural expression.